Two cases of granuloma faciale showing rosettes - Benedetta Sonego; Simona Sola; Giovanni Biondo; Cesare Massone (PAGEPress Publications, 2023)
Granuloma faciale (GF) is a rare benign chronic inflammatory dermatosis often difficult to distinguish clinically from other diseases, both inflammatory and neoplastic. Dermoscopy can be a helpful diagnostic tool and indeed several dermoscopic criteria observed in GF have been described in literature. We present two patients affected by GF in which we have observed rosettes.